Functional opsin retrogene in nocturnal moth. Issue 1 (December 2016) - Xu, Pengjun; Feuda, Roberto; Lu, Bin; Xiao, Haijun; Graham, Robert; Wu, Kongming
Abstract Background Retrotransposed genes are different to other types of genes as they originate from a processed mRNA and are then inserted back into the genome. For a long time, the contribution of this mechanism to the origin of new genes, and hence to the evolutionary process, has been questioned as retrogenes usually lose their regulatory sequences upon insertion and generally decay into pseudogenes. In recent years, there is growing evidence, notably in mammals, that retrotransposition is an important process driving the origin of new genes, but the evidence in insects remains largely restricted to a few model species. Findings By sequencing the messenger RNA of three developmental stages (first and fifth instar larvae and adults) of the pestHelicoverpa armigera, we identified a second, intronless, long-wavelength sensitive opsin (that we called LWS2). We then amplified the partial CDS of LWS2 retrogenes from another six noctuid moths, and investigate the phylogenetic distribution of LWS2 in 15 complete Lepidoptera and 1 Trichoptera genomes. Our results suggests that LWS2 evolved within the noctuid. Furthermore, we found that all the LWS2 opsins have an intact ORF, and have an ω-value (ω = 0.08202) relatively higher compared to their paralog LWS1 (ω = 0.02536), suggesting that LWS2 opsins were under relaxed purifying selection. Finally, the LWS2 shows temporal compartmentalization of expression. LWS2 inH. armigera in adult is expressed at a significantly lower level compared to all other opsins in adults; while in the in 1st instar stage larvae, it is expressed at a significantly higher level compared to other opsins. Conclusions Together the results of our evolutionary sequence analyses and gene expression data suggest that LWS2 is a functional gene, however, the relatively low level of expression in adults suggests that LWS2 is most likely not involved in mediating the visual process.